Proyecto de eval uaci ón para l a exportaci ón de fl ores ecuatori anas a la ciudad de mi ami – eeuu - Vera Cañarte, Juan P (2011)
In the present project it is realized a study of market and financial feasibility for the creation of an export and trading company of various types of flowers from various locations of Ecuador such as heliconias, ave de paraiso, Ginger, Anturio, maraca, mirto, roses and carnations in the Miami market. It includes the purchase of these species to domestic producers, brought to our warehouse, located in Guayaquil city, where the classification is carried out and then the packaging process starts at temperatures between 0 to 6 degrees Celsius; in order to be sent to Miami from José Joaquín de Olmedo International Airport in Guayaquil, using as transportation special aircrafts of Iberia airline. The motivation for this study lies in that the creation of this company achieves the many benefits of the ATPDEA treaty that have Ecuador with the US. This study includes a financial viability analysis to detail the costs involved in starting a business of this type and the expected income and thus, with financial criteria and based on market research, the convenience of the project.